COMPARISON OF MEAN C- REACTIVE PROTEIN LEVELS IN SMEAR POSITVE AND SMEAR NEGATIVE PULMONARY TUBERCULOSIS: C- Reactive Protein in Pulmonary Tuberculosis - Kashif, Muhammmad Ali, Sumreen (Pakistan Armed Forces Medical Journal, 2016)
Objective: To compare the mean C - reactive protein levels in clinically diagnosed adult patients with smear positive and smear negative pulmonary tuberculosis. Study Design: Cross sectional study. Place and Duration of Study: The study was conducted at the Department of General Medicine Military Hospital Rawalpindi from 21 May to 25 Sep 2011. Material and Methods: In this study 150 patients of clinically diagnosed pulmonary TB from either sex, age between 15 to 60 years who fulfilled the inclusion criteria were studied. They were divided in two groups, smear positive (sputum for AFB positive) and smear negative (sputum for AFB negative). Serum CRP sample was measured before antituberculosis treatment (ATT) was given. All data were analyzed using SPSS Version 17.0. Qualitative variables X-ray chest findings and gender have been presented as frequency percentage. Mean and standard deviation (mean ± SD) have been calculated for quantitative variables i.e. age, CRP levels in both groups. Mann Whitney - U test used to compare mean CRP levels in smear positive and smear negative cases of pulmonary TB. A p-value of <0.05 was considered significant. Results: The mean CRP levels were significantly higher in smear positive pulmonary tuberculosis 49.92 ± 10.25 mg/dl as compared to smear negative pulmonary TB 18.28 ± 6.18 mg/dl mean difference of 31.64mg/dl, p-value <0.0001. Mann Whitney - U test was used to compare the mean CRP levels of both groups. Conclusion: Serum CRP levels can be used as add-on with other investigations in pulmonary tuberculosis. Patients of smear positive tuberculosis have significantly higher serum CRP levels as compared to smear negative patients.